PENGARUH PEMANGKASAN TANAMAN SENGON TERHADAP KERAGAAN TANAMAN SELA DALAM SISTEM AGROFORESTRI SENGON - Abdul Hamid (BUANA SAINS, 2008)
The effects of pruning of Paraserianthes falcataria tree in an agroforestry system on yield of intercrops and tree performance were studied at Perhutani RPH Jatirejo, BKPH Pare, KPJH Kediri. Maize, stick nut, and chili were used as companion crops in between rows of two years old Paraserianthes falcataria tree. A split plot design with four replicates was set up for the experiment. The trees were 25%, 50% and 75% pruned. The measured parameters included growth and yield of the intercrops and performance of the tree. Results of this study showed that regular pruning of the agroforestry tree and planting of intercrops did not hinder growth and performance of the agroforestry tree, especially that was pruned 75%. Pruning of the tree also increase yield of the intercrops